Requirement and availability of feed and fodder resources for bovine population in Himachal Pradesh - VASHIST, G D; PATHANIA, M S (The Indian Journal of Animal Sciences, 2014)
Bovine population in the state recorded an increase at 12% between 1972 to 1992. The maximum increase was observed in buffaloes (25%). Between males and females both in cattle and buffaloes, female over 3 years of age showed positive growth rates. Percentage growth rate in the bovine population during different inter-census periods varied from -4.17 to 3.35. Among female cattle and buffaloes over 3 years of age the growth rate ranged from -3.17 to 5.91 and -4.74 to 8.66% respectively. A similar inter-district variation was observed in other categories of bovine population too. The findings of the study has amply demonstrated that there ex isted an overall shortage of all types of feed resources and the existing resources were not sufficient to meet even the half ofthe requirements of bovine stock in certain districts. There is an inter-district variation in the requirement and availability of feed resources in the state. There was a shortage of as much as of 50% of dry fodder, 21 % of green fodder and 94% concentrate in Himachal Pradesh in 1972, whereas corresponding estimated shortage for these feed stuffs by 2002 AD would be to the tune of 59,3 7 and 93% respectively. The gap between availability and requirement of feed resources for bovine will continue to exist and this would adversely affect the genetic potential particularly of crossbred cattle. In the past too, due to the shortage of feeds and fodder the crossbred cattle and upgrade buffalo have failed to portray their full genetic potential for higher production when fed at low levels. Therefore, timely steps ought to be taken on better feeding and management aspects to increase the production efficiency of the future population.